Portrait of Carlton "Dook" Sheffield. - unknown:::Creator::::::::::::
Portrait of Carlton 'Dook' Sheffield, Stanford roommate and long time friend. Inscription reads "Comme un petit chien qui espere a manger. A frere Dook" Translation "Like a little dog who hopes to eat. A brother Dook"